2016
DOI: 10.1097/pec.0000000000000927
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Foreign Body Ingestions

Abstract: Magnets are inherently attractive to young children, but present a risk when ingested. If consumed alone, small, smooth magnetic foreign bodies are likely to pass without significant event; however, ingestion of multiple magnets may have catastrophic consequences, including bowel perforation, obstruction, peritonitis, and death. Increasing reports of morbidity and mortality in recent years from the US National Electronic Injury Surveillance System has led to numerous safety statements from the American Academy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 24 publications
0
47
0
4
Order By: Relevance
“…Other studies also described intestinal obstruction from internal hernia and volvulus of intestine, fistula formation [10], and hemorrhage when the mesenteric was involved [10]. Midget J reported a twenty-month old boy who had ingested magnets, causing intestinal necrosis and abdominal sepsis, which led to death [11,12]. Additionally, Waters AM [13] reported another case of death due to the hemorrhage from an esophago-aortic fistula induced by ingestion of magnets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies also described intestinal obstruction from internal hernia and volvulus of intestine, fistula formation [10], and hemorrhage when the mesenteric was involved [10]. Midget J reported a twenty-month old boy who had ingested magnets, causing intestinal necrosis and abdominal sepsis, which led to death [11,12]. Additionally, Waters AM [13] reported another case of death due to the hemorrhage from an esophago-aortic fistula induced by ingestion of magnets.…”
Section: Discussionmentioning
confidence: 99%
“…Another investigation in 2013 reported that during 2002 and 2011, there had been more than 22,000 pediatric magnetic foreign body ingestion cases in America, and the investigation showed a 5-fold increase comparing the first and the last 2 years [4]. Rare-earth magnet, made from NdFeB (neodymium iron boron), a newly developed magnetic material, has a maximum magnetic energy force 5 to 10 times than that of the ordinary ferrite [12,15,16], suggesting that the tiny rare-earth magnet can produce a huge magnetic force. It was primarily developed for industrial Gastrointestinal mucosa erosion 28 37.8 -manufacturation such as electrical machinery, medical apparatus and instruments, in order to decrease the volume of production and enlarge its properties.…”
Section: Discussionmentioning
confidence: 99%
“…A particularly dangerous subset of magnets is small rare-earth magnets such as neodymium magnets, which are substantially stronger than traditional ferrite magnets [3,4]. Ingestion of multiple of these "supermagnets" is of special concern, as they can attract through intestinal walls, resulting in pressure necrosis, fistulization, and bowel perforation [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous cases of rare-earth magnet ingestion have been reported in the literature [4][5][6][7][8]. However, hypopharyngeal magnetic foreign body aspirations are less commonly described.…”
Section: Introductionmentioning
confidence: 99%
“…4) in the USA. [19,27] Examples of unresolved challenges to primary prevention locally and elsewhere include:…”
Section: Preventive Strategiesmentioning
confidence: 99%